2018
DOI: 10.1016/j.jcmg.2017.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Iron Within the Infarct Core After ST-Segment Elevation Myocardial Infarction

Abstract: ObjectivesThis study sought to determine the incidence and prognostic significance of persistent iron in patients post–ST-segment elevation myocardial infarction (STEMI).BackgroundThe clinical significance of persistent iron within the infarct core after STEMI complicated by acute myocardial hemorrhage is poorly understood.MethodsPatients who sustained an acute STEMI were enrolled in a cohort study (BHF MR-MI [Detection and Significance of Heart Injury in ST Elevation Myocardial Infarction]). Cardiac magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
11
33
1
Order By: Relevance
“…This might occur because of the fact that more severe MI and more severe ischaemia might lead to more cardiac dysfunction because of higher iron load and cellular oxidative stress. This is in line with studies which have revealed that persistent iron deposition in infarcted hearts is detrimental to cardiac function and is related to adverse outcomes …”
Section: Role Of Iron In Heart Diseasesupporting
confidence: 92%
See 1 more Smart Citation
“…This might occur because of the fact that more severe MI and more severe ischaemia might lead to more cardiac dysfunction because of higher iron load and cellular oxidative stress. This is in line with studies which have revealed that persistent iron deposition in infarcted hearts is detrimental to cardiac function and is related to adverse outcomes …”
Section: Role Of Iron In Heart Diseasesupporting
confidence: 92%
“…Preserving fine iron protein balance seems to protect the heart during MI. In addition, higher myocardial iron content is associated with lower EF and larger area of infarctions, while persistence of high iron content predicts the occurrence of HF . All these data have created the rationale for using chelation therapy in MI to prevent cardiac damage.…”
Section: Role Of Iron In Heart Diseasementioning
confidence: 99%
“…15 Carberry and colleagues 57 have recently confirmed these findings in a cohort of 203 STEMI patients. They showed that 36% of their cohort had intramyocardial hemorrhage by T2*-mapping and 59% of those had residual myocardial iron at 6 months.…”
Section: Recent Advances In the Role Of Cmr In Reperfused Stemi Patientsmentioning
confidence: 70%
“…Residual myocardial iron was associated with adverse LV remodeling at 6 months and worse clinical outcomes after a median follow-up of 4 years. 57 Figure 4a shows an example of a patient with an acute inferior STEMI treated by PPCI, and with late microvascular obstruction and intramyocardial hemorrhage despite restoring normal flow in the epicardial coronary artery during PPCI. At follow-up, there was residual myocardial iron and persistently elevated T2 values in the areas surrounding the residual iron, which may represent persistent myocardial inflammation.…”
Section: Recent Advances In the Role Of Cmr In Reperfused Stemi Patientsmentioning
confidence: 99%
See 1 more Smart Citation